ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR NO 3 KAYUBHI - I Nyoman Sudirman; I Wayan Lasmawan; I Wayan Suastra (Jurnal Lensa Pendas, 2024)
This research aims to analyze the implementation of the Independent Curriculum at SD Negeri 3 Kayubihi. The research approach used was descriptive qualitative with the subjects being class II students and class II homeroom teachers. Primary data was obtained through interviews with school principals, teachers and students, as well as classroom observations. Secondary data includes school documentation. The data analysis technique used is the Miles & Huberman model. The research results show that the Merdeka Curriculum at SD Negeri 3 Kayubihi has been implemented in accordance with government policy, including planning teaching materials, educational media, recording grades, diagnostic assessments, and teacher and student reflection. Differentiated education is applied to adapt teaching materials to student needs, so that education becomes more interesting and efficient. Comprehensive assessments include diagnostic, formative, summative and National Assessments. The challenges in implementing this curriculum were successfully overcome by teachers with creativity and thorough preparation. Overall, the implementation of the Independent Curriculum at SD Negeri 3 Kayubihi is going well, meeting government guidelines and student needs